Profile of HIV sero-positive attendees: an integrated counselling and testing centre record based retrospective study - Ade, Anju Damu; Yamasani, Bhavani; Deekala, Ravi Sankar; Kondagunta, Nagaraj; Katyarmal, Dnyaneshwar T. (International Journal Of Community Medicine And Public Health, 2018)
Background: The sustainable development goal target is to end the AIDS epidemic by 2030. HIV continues to be a major global public health issue, having claimed more than 35 million lives so far. The objectives of the study were to find out the pattern of socio-demographic profile among HIV sero-positive patients attending ICTC centre in SVIMS, Tirupati and to study the risk behaviour pattern among HIV sero-positives. Methods: Retrospective cross sectional study was undertaken at ICTC Centre, SVIMS, SPMC (W), Tirupati, Andhra Pradesh, India. The records of data of all the HIV sero-positive attendees who attended the ICTC from January 2013 to June 2018 were included as study subjects. Records maintained were noted in proforma containing socio-demographic characteristics of HIV seropositive patients. Data was analysed using SPSS software version 23.00. Results: Majority of sero-positives were illiterates, married, daily wage labourers from rural area, in 20 to 60 years age group. Transmission was predominantly through the heterosexual route (96.1%). 68(54.4%) males and 63(72.4%) females were sero-concordant while 57 (45.6%) males and 24 (27.6%) females were sero-discordant. Conclusions: There is need to carry out intense IEC activities for behavior change at grass root levels. Low literacy and limited access to health facilities should be addressed.